SOLUSI PROBLEMATIKA MAHASISWI PRODI KOMUNIKASI DAN PENYIARAN ISLAM SEKOLAH TINGGI ILMU BAHASA ARAB AR RAAYAH DALAM MENYELESAIKAN SKRIPSI - Hidayat, Tatang; Rahmi, Faddilatur; Istianah, Istianah (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
It is motivated by complaints from several KPI STIBA Ar Raayah study program students during the thesis completion process, and the cause of the delay of KPI students in completing the thesis. The purpose of this study is to analyze the solution to the problems of Islamic communication and broadcasting study program students of the Ar Raayah College of Arabic Language in Completing Thesis. In examining this problem, researchers used qualitative methods by conducting face-to-face interviews with several eighth semester students. Based on the results of the research, the problems of writing a thesis that occur come from the campus and also from the students themselves, the solution is to submit some suggestions and input to the campus, for students who experience obstacles from themselves can ask for help or motivation from friends and family.